2007
DOI: 10.1002/jez.417
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs between somatic and gonadal investments during development in the African clawed frog (Xenopus laevis)

Abstract: Tradeoffs between time to and size at metamorphosis occur in many organisms with complex life histories. The ability to accelerate metamorphosis can increase survival to the next life stage, but the resulting smaller size at metamorphosis is often associated with lower post-metamorphic survival or reduced fecundity of adults. Reduced fecundity is thought to be because of reduced energy reserves, longer time to maturity, or reduced capacity to carry eggs or compete for mates. This pattern could also be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Within species, the relative allocation to growth and reproduction generally appears to remain in stable proportion across wide levels of resource availability (Wootton ; McCoy et al. ; Inness & Metcalfe ; Zeng et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within species, the relative allocation to growth and reproduction generally appears to remain in stable proportion across wide levels of resource availability (Wootton ; McCoy et al. ; Inness & Metcalfe ; Zeng et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Within species, the relative allocation to growth and reproduction generally appears to remain in stable proportion across wide levels of resource availability (Wootton 1977;McCoy et al 2007; Inness & Metcalfe 2008;Zeng et al 2012). However, conditions experienced early in life may determine lifetime patterns in allocation to reproduction, while adult growth reflects prevailing conditions with deviations from a stable allocation ratio (Taborsky 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of plasticity in hatching are still relatively few, studies of plasticity in metamorphosis spanning more than 70 years have revealed that there are carryover effects of the larval environment even after crossing this life-history switchpoint (Pechenik 2006). Many taxa respond to larval conditions by altering their metamorphic phenotype (e.g., size, morphology, larval period duration; Werner and Gilliam [1984], Benard [2004]), which can have important consequences for post-metamorphic growth (Van Allen et al 2010), lifetime fitness (Semlitsch et al 1988, McCoy et al 2007, and population and community dynamics (Beckerman et al 2002, McCoy et al 2009). Such carryover effects have been demonstrated in bryozoans, gastropods, polychaetes, crustaceans, echinoderms, urochordates, insects, and amphibians (reviewed in Pechenik 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Development during the larval period and sweeping changes in the internal anatomy of organisms during metamorphosis provide an opportunity for individuals in good habitat to invest in higher quality tissues (Zera and Harshman 2001;Ishizuya-Oka and Shi 2005;Brown and Cai 2007). For example, Xenopus larvae reared at higher food levels metamorphosed with larger and more developed gonads (McCoy et al 2007). This is likely due to a portion of increased larval food being used for reproductive rather than somatic growth.…”
Section: Discussionmentioning
confidence: 97%